Registration of Copyright as Guarantee of Batik Motif Legal Protection (Comparation Study of Indonesia, Malaysia and Thailand) - Agustina Balik; Yosia Hetharie; Novyta Uktolseja; Putri Anggia; Revivo Tulaseket (Universitas Negeri Semarang, 2023)
This study aims to identify and analyze the legal protection of Kei batik motifs through copyright registration and the role of local governments in providing legal protection for these Kei batik motifs. This research is a sociolegal research, which is a combination research method between doctrinal legal research methods and empirical legal research methods. Based on the results of the research, Camelia Batik Kei's business raised batik motifs based on the philosophical customs and culture of the people of the Kei Islands. In the aspect of intellectual property rights, Batik Kei has not been touched at all either through the awareness of the business actors themselves or the local government. Even though the Kei Batik motif with the traditional and cultural characteristics of the Kei people is very promising from the aspect of business development, that's why legal protection through registration of intellectual property rights in the field of copyright is very important. The Government of Indonesia, should also play an important role in terms of contributing through mentoring and empowering businesses of this kind which of course do not only provide economic and moral benefits to creators but also to the region and the people of Kei. When compared to neighboring countries such as Malaysia and Thailand which also have works of art in the form of batik, Indonesia has a variety of batik motifs with different styles between regions. Therefore, good legal protection is needed so that it is not claimed by other parties or even other countries.